ANALISIS PENDAPATAN USAHATANI SAWI (Brassica juncea L.) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Yan Yosef Agus Suratman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This study aims: (i) to obtain a description of how to plant mustard; (ii) to find out how big the cost of explicit, revenue, and income of mustard farming in the village of North Landasan Ulin, Liang Anggang Subdistrict. The method used in this research is survey method with observation technique, where sampling technique (sample) is done by simple random sampling  from 80 households is taken 38%, so that obtained by 30 respondents. The results showed that the average yield of mustard was 2,589,60 bunch / respondent or 645,15 kg / respondent, the average explicit cost Rp 1,873,237.15 / respondent, the average revenue Rp 7,741,800,00 / responder and income average Rp 5,868,562.85 / respondent